Research on distribution performance of desert sand for heat storage in downcomer. Issue 2 (26th January 2018) - Zhu, Guihua; Lv, Shuo; Jiang, Feng; Tan, Dongyang; Zhang, Jisheng; Zhao, Ying; Mu, Shuogui; Yan, Yongqiang; Liang, Songquan
ABSTRACT: In this research, desert sand is used as the sensible heat storage medium, which exchanges heat with air in the downcomer to realize heat storage and heat release. The desert sand distribution uniformity has a significant impact on the heat exchange performance and efficiency between desert sand and air for the process of convection in the downcomer. Given the superiority of sensible heat storage in convective heat transfer between desert sand and air, distributors with cylinder or conical bore solid particles and homogeneity performance testing device are designed and manufactured on the basis of convection system equipped with solid particle–air downcomer. Then, the convection experiment between solid sand and air is researched. The greater the desert sand flow rate and higher the volume density, the larger the variance of regional mass flow rate and the worse the homogeneity performance. For the cylinder bore distributor, the smaller the sand particle size is, the greater affected the sand groups can be. The sand homogeneity performance is preferable with the two particle size ranges: 0.18-0.25 mm and 0.15-0.18 mm. The total sand flow rate decreases, but the uniformity improves with the increase of the air flow velocity, and the best distribution performance is achieved at an air velocity of 0.6 m/s. However, the distribution performance declines with the air flow velocity persistently increasing because the sand groups are pushed to one pipe side close to the wall. The sand groups deflect seriously with the air flow velocity increasing.